Lightning Location, NOx Production, and Transport by Anomalous and Normal Polarity Thunderstorms. Issue 15 (9th August 2019) - Davis, Trenton C.; Rutledge, Steven A.; Fuchs, Brody R.
Abstract: Production and transport of NOx by convection is critical as it serves as a precursor to tropospheric ozone, an important greenhouse gas. Lightning serves as the largest source of nitrogen oxides (NOx = NO + NO2 ) to the upper troposphere (UT) and is one of the largest natural sources of NOx . Interest is placed on the vertical advection of NOx because its lifetime increases to several days in the UT compared to roughly 3 hr in the lower troposphere and boundary layer. Thus, lightning can play an important role in ozone production within the UT. However, the amount of NOx produced per flash and NOx advection in storms remain uncertain. This study investigates lightning NOx (LNOx ) production and transport processes in anomalous (midlevel positive charge) and normal polarity (midlevel negative charge) thunderstorms by advecting parcels containing LNOx from the flash channels of over 5, 600 lightning flashes observed during the Deep Convective Clouds and Chemistry (DC3) field campaign. Results reveal that most flash channels occur near 6‐8 km in the normal polarity thunderstorms and 5‐6 km within anomalous polarity thunderstorms. Larger flash rates and stronger updrafts in anomalous storms result in considerably larger LNOx mixing ratios (peaks of 0.75‐1.75 ppb) in the UT compared to normal polarity storms (peaks < 0.5 ppb). A slightly lower mean flash LNOx production was also found among all five storms in this study (storm mean values of 72‐158 moles per flash) compared to previous estimates, which generally parameterize LNOx by flash rate rather than flash count. Key Points: Flash channels are derived from LMA observations to generate lightning‐produced NOx in air parcels of normal and anomalous polarity storms Higher flash rates and stronger updrafts lead to a striking increase in LNOx transport to the upper troposphere in anomalous storms LNOx produced by compact flashes are slightly lower than previous estimates of LNOx produced per flash